An Assessment of Information Resources in Marine Sciences in India - Bhatt, V. S. (Journal of Information and Knowledge, 1978)
Reports the findings of a survey of the Marine Institutional Information Resources/Services in India. Questionnaire method has been adopted for the collection of information. Suggests the establishment of a full-fledged National Oceanographic Information Centre having linkage with Inter-governmental Oceanoraphic Commission and World Data Centres.